Strategi Peningkatan Ekonomi Bumdes Seresam Melalui Pemberdayaan UMKM - Enni Savitri; Tressy Fitri; Aura Abiyyi; Akrom Mahdi Mahdi; Shafira Aprilia; Doni Hadiguna; Bryan Yohannes; Lathif Fathony; Rizki Rahmayana; Rhumeta Rhumeta; Alia Afifah (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
Village-Owned Enterprises (VOE) are one of the institutions that have the ability to improve the welfare of rural communities. VOE also act as partners for Micro, Small, and Medium Enterprises (MSMEs). To help improve the economy of  Seresam Village’s VOE, student community service (SCS) of Riau University carried out economic-based activities, especially in empowering MSMEs in Seresam Village, Indragiri Hulu Regency on July 12, 2022. The target community in this activities is MSMEs in Saresam Village, Indragiri Hulu Regency, Riau. This economic-based activity carried out using survey methods for MSMEs, creating whatsapp group, revitalizing MSMEs trade stalls and installing banners as a marketing tool. The result of this activities is an increase in the marketing of MSMEs products and restore the VOE’s field as a center for MSMEs.